Implementing Environmental Education in the Curricular Strategy at Tertiary Education from the Perspective of Mathematics - Bande González, Libán; Del Sol Martínez, Jorge Luis (My University, 2022)
Environmental education has become a vital topic in schools nowadays. From primary school to tertiary education, environmental education can be taught in every subject because of its versatility. However, in some universities this is not the case and some students ignore how their majors can contribute to raise their environmental education. The present work is directed to improve the performance of the students at the university level by designing and implementing teaching tasks to raise both their culture and their environmental education from the perspective of Mathematics. Some methods were applied in order to analyze the current design of the Curricular Strategy used in tertiary education and to determine how environmental education should be implemented in the Curricular Strategy without affecting its structure. Problems of differential equations from the discipline of Higher Mathematics were used as an alternative supported by a psycho-pedagogical approach. The exercises achieved the purpose stablished by the authors. Teaching tasks based on everyday life allow the students to understand the essence and get a more global vision of the object of study. This research was considered as a valid contribution for the confection of new curricular strategies and it also served as a basis to inspire some other works from the perspective of Physics and Biology.
Keywords: Environmental Education; Curricular Strategy; Higher Mathematics; Teaching Tasks